Macrophages in Osteosarcoma Immune Microenvironment: Implications for Immunotherapy - Luo, Zhong-Wei; Liu, Pan-Pan; Wang, Zhen-Xing; Chen, Chun-Yuan; Xie, Hui (Frontiers in Oncology, 2020)
Osteosarcoma is a malignant primary bone tumor commonly occurred in children and adolescents. The treatment of local osteosarcoma is mainly based on surgical resection and chemotherapy, whereas the improvement of overall survival remains stagnant, especially in recurrent or metastatic cases. Tumor microenvironment (TME) is closely related to the occurrence and development of tumors, and macrophages are among the most abundant immune cells in the TME. Due to their vital roles in tumor progression, macrophages have gained increasing attention as the new target of tumor immunotherapy. In this review, we present a brief overview of macrophages in the TME and highlight the clinical significance of macrophages and their roles in the initiation and progression of osteosarcoma. Finally, we summarize the therapeutic approaches targeting macrophage, which represent a promising strategy in osteosarcoma therapies.